2011
DOI: 10.4049/jimmunol.1002998
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated a2 Vacuolar ATPase Acts As a Key Mediator of Cancer-Related Inflammation by Inducing Pro-Tumorigenic Properties in Monocytes

Abstract: Cancer-related inflammation profoundly affects tumor progression. Tumor-associated macrophages (TAMs) are known regulators of that inflammation, but the factors that initiate cancer-related inflammation are poorly understood. Tumor invasiveness and poor clinical outcome are linked to increased expression of cell surface-associated vacuolar adenosine triphosphatases. The a2 isoform vacuolar adenosine triphosphatase is found on the surface on many solid tumors, and we have identified a peptide cleaved from a2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(70 citation statements)
references
References 63 publications
4
66
0
Order By: Relevance
“…Our previous studies showed that the key portion of the a2V protein is a2NTD, the N-terminal portion that is released from the activated monocyte and induces the cytokines secretion (Kwong et al 2011). In this study, we showed that capacitated sperm secrete a2NTD in the surrounding milieu.…”
Section: V-atpase Induces Immune Responses Of Pregnancysupporting
confidence: 49%
See 3 more Smart Citations
“…Our previous studies showed that the key portion of the a2V protein is a2NTD, the N-terminal portion that is released from the activated monocyte and induces the cytokines secretion (Kwong et al 2011). In this study, we showed that capacitated sperm secrete a2NTD in the surrounding milieu.…”
Section: V-atpase Induces Immune Responses Of Pregnancysupporting
confidence: 49%
“…Previously, we have shown that a2V can regulate IL1B as well as IL1A with little or no subsequent increase in TNF secretion (Ntrivalas et al 2007, Kwong et al 2011. This process appears to occur by two different mechanisms.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Tumor cells consistently release immunosuppressive and proinflammatory factors that facilitate tumor immune-escape and tumor progression (20,21). In contrast, tumor-surrounding cells, such as dendritic cells, also secrete certain factors to modulate the development of cancer (22).…”
Section: Discussionmentioning
confidence: 99%